The Power of Love and Resilience: Boosting Work Engagement in Elite Combat Unit of the Indonesian Air Force - Aulia Aulia; Audrina Ardianty; Reza Tamafaya Aprilia; Zaenal Wafa (Journal of Educational, Health and Community Psychology, 2023)
Kopasgat is one of the elite combat units of the Indonesian Air Force. As a combat unit that has work demands and high work consequences or risks, it will affect the work engagement of members. While work engagement has an important role in work life because it has a very significant impact on individual and organizational performance as a whole. Thus the aim of this research is to test empirically the effect of love of work and resilience on work engagement. This study uses a quantitative approach with a correlation design. The population in this study were members of the Kopasgat Denhanud 474 Yogyakarta. The sampling technique used in this study was a purposive technique, so that the sample in this study were 127 members of the Yogyakarta Special Forces Denhanud 474 who were in the Air Assault Batteries unit (PSU Batteries). The instruments used in this study were the Utrecht Work Engagement Scale (UWES), the love of work scale and the resilience scale. The results of multiple linear regression analysis showed a coefficient value of R=0.848, F=158.712 (p<0.01). The results of this study indicate that love of work and resilience have a very significant influence on the work engagement of members of the Kopasgat Denhanud 474 Yogyakarta. This research contributes to the field of military psychology by highlighting the importance of love of work and resilience to increased work engagement which will have implications for improving the performance of combat unit members. This is especially relevant in the Indonesian context, where the military plays an important role in national security and defense.